Illustrations of political economy, Volume 5 (of 9) - Martineau, Harriet, 1802-1876 (Salt Lake City, UT : Project Gutenberg, 2023)
"Illustrations of Political Economy, Volume 5" by Harriet Martineau is a narrative work written in the mid-19th century. This volume serves as part of a larger series aimed at exploring the principles of political economy through fictional narratives. The opening chapters introduce a group of Polish exiles navigating the harsh wilderness of Siberia, interlacing themes of oppression, personal sacrifice, and the pursuit of freedom against the backdrop of political turmoil. At the start of the narrative, the reader is plunged into a grim scene where Russian officers escort Polish prisoners toward their grim fate in Siberia, setting a somber tone. The characters are lively, yet burdened with their struggles; for instance, Taddeus, who has crippled himself to avoid conscription, and his sister Sophia, who grapples with resentment and grief following their exile. The dynamic among family members reveals deep emotional scars as they journey through a landscape symbolic of their lost homeland and shattered lives. Through their intertwined fates against the chilling expanses of Siberia, Martineau explores broader themes of loss, national identity, and the resilience of the human spirit amidst adversity, firmly rooting the tale in the socio-political context of its time. (This is an automatically generated summary.)
The charmed sea -- Berkeley the banker.
Release date is 2023-11-02
Emmanuel Ackerman, KD Weeks and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Social problems -- Fiction; Didactic fiction, English; Political fiction, English